Land cover diversity: Reshaping the socioeconomic value of land. (15th April 2023) - Chen, Yahan; Wang, Xin; Xie, Zongqiang
Abstract: The land is a vital resource to support economic growth. Previous studies have mainly taken urban and agricultural areas as the major factors of economic boost. However, the supporting role of diversified land in sustainable economy has not been fully valued. This study analyzed the relationship between land cover diversity and socioeconomic outputs from 1992 to 2019 on up to 2086 counties in China. The results showed the regional disparity in the eastern and western counties. In the western counties, land cover diversity was positively correlated with per area socioeconomic indicators throughout the period. In the eastern counties, the correlation with per area indicators has gradually changed from negative to positive. The correlation with per capita indicators was more significant in the east than west. The regional disparity and temporal trends may come from the influence of water resources, demographic pressure and other constraints in different regions. The refreshed land value can help to achieve sustainable development and improve human well-being in the long term. Highlights: Land cover diversity plays an essential role in socioeconomic development. Regional disparity was discovered in the eastern and western counties in China. Land cover diversity is related to status per area in regions with water shortage. Land cover diversity is related to status per capita in regions under demographic pressure.